Effect of alcoholic beverages on progeny and reproduction of mice - Fernanda Dias Figueiro; Ana Clara Cerato Bispo; Karla Lorena Guarido; Priscila Marianno; Gabriel de Araújo Costa; Helena Kaminami Morimoto; Maria José Sparça Salles (Universidade de São Paulo, 2018)
ABSTRACT Alcohol is the most commonly consumed substance in the world. The objective of this study was to evaluate the influence of alcoholic beverages on male reproduction and possible alterations in their offspring. The mice were divided into 4 groups: beer, wine, cachaça (a type of sugarcane rum), with ethanol concentrations of 1.9 g/kg, and control group treated with PBS. The treatment period was 35 days. The animals which received cachaça, demonstrated significant weight loss in the testes and epididymis. The alcoholic beverages promoted significant testosterone level and fertilization index diminution, and morphological alterations in the spermatozoa. The beer group presented decreased implantation sites and a high frequency of dominant lethal. The number of reabsorptions in the wine group was increased. The fermented beverages presented higher potential to induce visceral malformations, while the cachaça caused fetal skeletal malformations. The cachaça treated group presented a negative impact on semen quality and fertilization potential. The treatment with different alcoholic beverages, during spermatogenesis, demonstrated contrasting degrees of induction of toxic effects, interfering in a general aspect in male reproductive performance, fetal viability during intrauterine life, and birth defects. From the data, it is possible to infer that the distillated beverage caused more harmful effects to reproduction in this study.